Geographical Assessment of Village Settlements in Düzce Akçakoca District - Olğaç, İrem; Doğan, Mesut (Fırat University, 2024)
Akçakoca, which constitutes the study area, is a province of Düzce and is located in the Western Black Sea coastal zone. Akçakoca district has a surface area of 380 km². In Akçakoca district, which is surrounded by natural borders, the slope generally increases from west to east and from north to south. The district is connected to important megapolis and metropolis such as Istanbul and Ankara via the TEM highway via Düzce. In the study, rural settlements of the Akçakoca district were examined from a geographical perspective. While it is an important resource for different fields by evaluating the results obtained, it also contributed to the updating of existing information. Data sources of the study; it was obtained from field studies conducted at regular intervals, electronic media, and official institutions and organizations. The resulting results were processed with various programs and supported with tables, graphs, and maps. The main subject of the study is the 43 village settlements of the district. Most of these village settlements were established below 100 m. altitude. It has been determined that the elevation levels of the villages in the study area are relatively evenly distributed. Villages are generally located at the edge of the forest, on the slope, by the river, and by the intercity road. While 20 of the village settlements are collective, 23 are dispersed. Economic activities in village settlements are shaped around agriculture, animal husbandry and tourism activities. The minimum population in the villages in the study area is 97 people and the highest is 736 people. The rate of villages with a population of 200-300 was determined as 41,86%.

Çalışma sahasını oluşturan Akçakoca, Düzce iline bağlı olup Batı Karadeniz kıyı kuşağında yer almaktadır. Akçakoca ilçesi 380 km² yüz ölçüme sahiptir. Doğal sınırlarla çevrili olan Akçakoca ilçesinde eğim genel olarak batıdan doğuya, kuzeyden güneye doğru artış göstermektedir. İlçe, Düzce üzerinden TEM otoyoluyla İstanbul ve Ankara gibi önemli megapol ve metropolle bağlantı kurmaktadır. Çalışmada, Akçakoca ilçesinin kırsal yerleşmeleri coğrafi bir bakış açısıyla incelenmiştir. Elde edilen sonuçların değerlendirilmesiyle farklı alanlara yönelik önemli bir kaynak olmakla birlikte mevcut bilgilerin güncellenmesi de katkı sağlamıştır. Çalışmanın veri kaynakları; belirli aralıklarda yapılan arazi çalışmalarından, elektronik ortamlardan, resmi kurum ve kuruluşlardan temin edilmiştir. Ortaya çıkan sonuçlar çeşitli programlarla işlenerek tablo, grafik ve haritalarla desteklenmiştir. Çalışmanın temel konusunu ilçenin sahip olduğu 43 köy yerleşmesi oluşturmaktadır. Bu köy yerleşmelerinin büyük bir kısmı 100 m. yükselti basamağının altında kurulmuştur. Çalışma sahasında yer alan köylerin, yükselti basamakları nispeten dengeli bir şekilde dağıldığı tespit edilmiştir. Köyler genel olarak orman kenarında, yamaçta, nehir kenarında ve şehirlerarası yol kenarında konumlanmıştır. Köy yerleşmelerinin 20’si toplu iken 23’ü dağınık formdadır. Köy yerleşmelerindeki ekonomik faaliyetler tarım, hayvancılık ve turizm faaliyetleri etrafında şekillenmiştir. Çalışma sahasındaki köylerde nüfus en düşük 97, en yüksek ise 736 kişiden oluşmaktadır. Nüfusu miktarı 200-300 arasında olan köylerin oranı %41,86 olarak tespit edilmiştir.
DÜZCE AKÇAKOCA İLÇESİNDE KÖY YERLEŞMELERİNİN COĞRAFİ AÇIDAN DEĞERLENDİRİLMESİ
Keywords: Environmental Management (Other); Çevre Yönetimi (Diğer)